The Sustainability in Civil Construction Waste Management in Brazil - Teresa Alejandra Diaz Figueroa , María; Kevin Calvay Pinedo, Franz (National Journal of City Management, 2022)
By the year 2050, there is a projected growth of 66% in the world urban population, and in the year 2030, 41 megalopolises are estimated with more than 10 million inhabitants. Considering the accelerated urbanization and the amount of waste generated in the cities only increases, the disposal of construction waste in inappropriate places contributes to the degradation of the environmental quality. In the 2010-2019 period, there was a quantitative increase in these residues, from 33 million tons in 2010 to 44.5 million in 2019. The large volume has led city halls to spend a large amount of public resources on their collection, treatment and final disposition. Despite the existence of laws, those responsible ignore it, harming the environment and increasing the amount of illegal dumps. The main objective of this article is to study the sustainable development of waste management generated by civil construction in Brazil through a bibliographic review gathering the ideas and information in a single document. In addition, there are negative environmental impacts and their assessment helps environmental management programs and quantifies how much they can impact environmental quality and human health. Likewise, it was evidenced that the integration of technology and smart solutions in the waste management process brings with its innovations that facilitate the tasks of the projects and decision-making, generating value for each project related to the civil construction and construction activities. Contribute efforts to achieve the goals of sustainable development, especially those directly related to the construction sector.